Improving Students’ Speaking Performance By Using Autoplay Media At Smas Darul Hikmah Mataram - Edi Firman; Ahmad Hanan (Mandala, 2019)
This research was aimed to describe the use of Auto-play Media to Improve Students’ Speaking Performance at SMAS Darul Hikmah Mataram. This research was classroom action research and focused on improving of the students’ speaking performance by using Auto-play Media. This research consisted of one cycle including all aspects of classroom action research model such as: planning, acting, observing, and reflecting. In this research, the researcher took the XI IPS of SMAS Darul Hikmah Mataram. The instrument that used by the researcher in this study were test, observation and recording to measure the students speaking performance in deep analysis model. Based on the result of data analysis, the mean score of students’ achievement during the primary observation was 45.05, meanwhile on pre-test and the percentage was merely 21.05% and post-test showed the students speaking performance increased into 79.36, with percentage score was 78.94%. Therefore, the researcher concluded that the score of the students’ speaking performance was increased after treated using auto-play and it was higher than minimum Complete Criteria Success (KKM), in which the KKM of SMAS Darul Hikmah Mataram was 75. Therefore, it could be underlined that this research was successfully in increasing the students’ speaking performance especially at SMAS Darul Hikmah Mataram